Tinjauan Atas Kebijakan Hukum Pidana Terhadap Penyuapan Di Sektor Privat Dalam Hukum Nasional Indonesia: Suatu Perbandingan Dengan Singapura, Malaysia Dan Korea Selatan - Prahassacitta, Vidya (Jurnal Hukum & Pembangunan, 2017)
Purpose of this research is to analyze private sector bribery penal policy in Indonesia. Although Indonesia ratified United Nation Convention Against Corruption, Indonesia has not implemented the convection’s provision of article 21 regarding the criminalization of private sector bribery. Analysis conducted using a functional method of comparative law from Konrad Zweigert and macro comparison against private sector bribery penal, which successfully applies in Singapore, Malaysia, and South Korea. Therefore, reflected from private sector bribery penal policy in Singapore, Malaysia, and South Korea thus Indonesia shall reformulate the private sector bribery provision which regulates in in current corruption act draft.